Clinical features, disease activity and outcomes of Malaysian children with paediatric systemic lupus erythematosus: A cohort from a tertiary centre. (August 2020) - Lim, Sern Chin; Chan, Elaine Wan Ling; Tang, Swee Ping
Background: Paediatric systemic lupus erythematosus is a rare autoimmune disease with a wide spectrum of clinical presentation in different populations. We present a cohort of paediatric systemic lupus erythematosus in Malaysia where the disease features and outcomes are still largely unknown. Methods: A retrospective review of all paediatric systemic lupus erythematosus patients with at least 6 months follow-up at Selayang Hospital from 2004 to 2016. Epidemiological, clinical and outcome data were collected and analysed. Results: A total of 141 paediatric systemic lupus erythematosus patients, 87.9% females, were followed up for a median 6.3 years (interquartile range 3.6–9.0). The median age at diagnosis was 10.8 years (interquartile range 9.0–12.0 years), positive family history of systemic lupus erythematosus was present in 12.1% and the majority (61.7%) were of Malay ethnicity. Common presentations included fever (87.2%), vasculitic rash (72.3%) and lethargy (69.5%). At diagnosis, leukopenia (51.1%), thrombocytopenia (41.8%) and cutaneous lupus (56%) predominate with significant renal involvement (39.7%). Renal (45.4%), liver (26%) and the central nervous system (17%) were important major organs involved during the course of the disease. At diagnosis, almost all (99.3%) patients had high disease activity (mean Systemic Lupus Erythematosus Disease Activity Index score 20.1 ± 9.6). The majority (62.4%) achieved remission or low disease activity after 6 months, maintained over the next 10 years. Damage occurred early (39.1% at 1 year) and increased with time. Ocular damage was the most common side effect (29%) and was predominantly corticosteroid related (93%). Growth retardation was significant (38.2%) with no gonadal failure or secondary malignancies. End-stage renal disease occurred in 3.1% patients whereas 53.1% had sustained renal remission. Overall mortality was 1.4%. Conclusion: Despite high disease activity at diagnosis, the majority had good sustained response to treatment with low overall mortality. However, there was progressive accrual of organ damage, highlighting the need for further research and refinements into therapies for paediatric systemic lupus erythematosus.